FINDING AUTHENTICITY THROUGH STORYTELLING: REFLECTIONS FROM A HIGH SCHOOL CLASSROOM - Liu, Joey Yung-Jun (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2019)
This piece is an auto-biographical reflection on my year-long experience creating a new course called Oral Interpretations and Expressions. Teaching the course allowed me to find an authenticity and identity in my work, which had been eluding me as I conformed to administrative norms in education. Through the practice of story-telling in spoken word poetry, my students and I found healing and transformation. This note invites the reader to consider how story-telling might be used in their own teaching spaces to empower a deeper connection to authenticity within themselves and their students.